Actual of doping test among top athletes and gender differences - Nishikori, C.; Kubo, Y.; Dohi, M. (Journal of High Performance Sport, 2019)
The purpose of this study was to clarify the actual state of doping test among top athletes. This survey was conducted among 221 athletes aged =20 years (121 men and 100 women) who underwent medical checkups at clinics run by the Japan Sport Council and who had previous experiences in undergoing doping tests. To understand the current situation in doping testing among athletes, a questionnaire survey was conducted from the perspective of "prevention of the adverse effect of dop-ing tests on the condition of athletes."Our findings confirmed that when undergoing doping tests, some athletes experienced stress and unpleasant feelings during urine collection and other situations related to the test. In addition, our findings also indicated that doping tests had an effect on the deterioration of athletes` conditions.In addition, because doping tests using urine collection may also pose substantial psychological and physiological burdens on some athletes, testing methods other than urine collection are also meaningful from the perspective of conditioning in preparation for competitions. Our study shows that methods other than the currently mainstream urine collection should be attempted in the sample collection for doping tests and that a system should preferably be put in place that allows for athletes themselves to select a sample collection method depending on their circumstances.